EDUCATION AS A VALUE DOMINANT IN THE EDUCATION OF YOUTH - Rusyn, Halyna (Mountain School of Ukrainian Carpaty, 2019)
The article reveals the basic concepts of «value», «value orientation», «spiritual and cultural value of education». Education in higher education institutions should systematize and deepen the life experience of young people. That is a certain basis of the spiritual world of personality. They reflect the attitude of man to the world, to himself and influence the activity of man in society, bringing meaningto his life. Due to value orientations, young people are mastered by the achievements of the spiritual culture of society. The content of education is enriched through the accumulation of knowledge about the world, which is assimilated by man in the process of forming certain value orientations in her. This knowledge contributes to a better understanding of values and traditions of other cultures by people and promotes the formation of a new system of positive values among students. Education becomes the main tool for forming the harmonious inner world of the student's personality, contributes to the further development of his abilities to quickly find a way out of a variety of conflict situations, both personal (internal spiritual, moral) and social content. It greatly enhances the ability of a person to actualize the personally necessary parameters for life in the modern world such as spiritual integrity, activity and autonomy, gradually combining them into a certain system of agents that have a positive effect on the procesd of self-realization of the individual in the realities of the modern world which is constantly changing. Therely significantly minimizing the probability of occurrence of a feeling of insecurity of the individual, which arises after receiving a large amount of negative information. Education is the part of the spiritual culture of the individual and influences the formation of the moral record of a person, promotes the further development of his spiritual world, abilities and creative potential of the individual. It is extremely important to draw attention to the need to form the spiritual and cultural values of education of modern students, which will become the basis for the translation of the development of a harmoniously and comprehensively developed, broad-minded, spiritually and culturally educated personality.